Comparative study of quality of life, adverse effects after cytoreduction and HIPEC in stage IIIA-IIIC ovarian cancer - Rybin, A. I.; Maksymovskyj, V. Y.; Pyrogov, V. V.; Demidchik, R. Ya.; Varabina, A. O. (Journal of Education, Health and Sport, 2018)
Nowadays cytorective surgery and HIPEC is the mainstay of management of advanced stages ovarian cancer. Study was conducted to assess the effectiveness of combined treatment in IIIA-IIIC ovarian cancer, its impact on quality of life. 37 patients of main group (CRS + HIPEC) were compared with 25 patients of control group (surgery + systemic chemotherapy). The quality of life was assessed with Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). Comparative analysis of quality of life 6 months after treatment completion did not show significant statistical difference. Combination of cytoreduction with HIPEC improves quality of life in patients with ovarian cancer, is tolerated better and has less systemic toxicities than systemic chemotherapy.